Логические методы расчета надежности - Levin, V. I. (PE "Politekhperiodika", Book and Journal Publishers, 2010)
An automatical-logical model of system reliability has been introduced. Automaton's input processes model safety processes in system packages, and the it's output processes model safety processes inside system itself.